1999
DOI: 10.1111/j.1600-0447.1999.tb10832.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities in schizophrenic patients: a prospective follow‐up study 5 years after first admission

Abstract: Madsen AL, Vorstrup S, Rubin P, Larsen JK, Hemmingsen R. Neurological abnormalities in schizophrenic patients: a prospective follow‐up study 5 years after first admission. Acta Psychiatr Scand 1999: 100: 119–125. © Munksgaard 1999. Objective: The aim of this study was to examine the temporal stability of neurological abnormalities in first‐episode schizophrenic patients, and to clarify the relationships between such abnormalities and psychopathology. Method: A total of 18 schizophrenic patients, 11 non‐schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 23 publications
8
61
0
1
Order By: Relevance
“…A number of crosssectional studies did not find an association between neurological soft signs and illness length (e.g., Gupta et al, 1995;Ismail, Cantor-Graae, Cardenal, & McKeil, 1998;Venkatasubramanian et al, 2003;Chen, Lam, Chen, & Nguyen, 1996). However, Yazici, Demir, Yazici, and Gogus (2002) Madsen, Vorstrup, Rubin, and Larsen (1999) found a higher incidence of neurological abnormalities over a five-year period. Given that patients with unremitting symptoms also received higher or more continuous doses of medication, it is difficult to disentangle the effects of symptom course and severity from the consequences of medication (Bombin et al, 2005).…”
Section: Neurological Soft Signs and Schizophreniamentioning
confidence: 97%
“…A number of crosssectional studies did not find an association between neurological soft signs and illness length (e.g., Gupta et al, 1995;Ismail, Cantor-Graae, Cardenal, & McKeil, 1998;Venkatasubramanian et al, 2003;Chen, Lam, Chen, & Nguyen, 1996). However, Yazici, Demir, Yazici, and Gogus (2002) Madsen, Vorstrup, Rubin, and Larsen (1999) found a higher incidence of neurological abnormalities over a five-year period. Given that patients with unremitting symptoms also received higher or more continuous doses of medication, it is difficult to disentangle the effects of symptom course and severity from the consequences of medication (Bombin et al, 2005).…”
Section: Neurological Soft Signs and Schizophreniamentioning
confidence: 97%
“…NSS are minor ("soft") neurological abnormalities in sensory and motor performance identified by clinical examination. In a follow-up study by Madsen et al 36 , a significant increase in the number of neurological abnormalities was observed in a group of males five years after the onset of the first psychotic episode. Nevertheless, results from studies with schizophrenia patients were not consistent with respect to the differences in gender and NSS.…”
Section: Premorbid and Prodromic Variablesmentioning
confidence: 99%
“…Studies in patients with a first psychotic episode have shown a possible relationship between the presence of Neurological Soft Signs (NSS) and the male gender 36 . NSS are minor ("soft") neurological abnormalities in sensory and motor performance identified by clinical examination.…”
Section: Premorbid and Prodromic Variablesmentioning
confidence: 99%
“…A large number of studies now suggest that these signs are already present at the time of the first psychotic episode [4,[10][11][12][13], although the mean scores may be even higher in subjects at more advanced stages of the illness [14], where worse neurological dysfunction could be a consequence of the progression of the disease. Although significantly lower than those of patients, NSS are also present in healthy individuals from the general population, with rates varying from 5% [15,16] to more than 50% [17,18], the proportion reported being mainly a function of the measure used.…”
mentioning
confidence: 99%